Surface Contamination in a Teaching Hospital: A 6 Year Perspective - Roland Christel; Ouellette-Frève; Plante Caroline; Bussières Jean-François (De Gruyter, 2016)
The aim of this paper is to review the surface contamination of three hazardous drugs within a teaching hospital and comment the different strategies put in place over the years in the context of these multicenter studies.